Unraveling the Interaction of Work Environment, Work-Life Balance, Perceived Organizational Support, and Career Anxiety among Female Workers - Nova Erin Kismiati; Muhafidhah Novie; Wahyu Eko Pujianto; Ayu Lucy Larassaty (Journal La Sociale, 2024)
Women play a crucial role in workforce growth and can contribute to identifying and addressing gender inequality in the workplace. Women play a crucial role in workforce growth and can contribute to identifying and addressing gender inequality in the workplace. Women play a crucial role in workforce growth and can contribute to identifying and addressing gender inequality in the workplace. However, they also face significant challenges in balancing work and personal life. This study utilized a causal approach and collected data through questionnaires. The study utilized SPSS software for analysis and the Hayes model 65 process macro to evaluate the proposed hypotheses. The results indicate a positive and significant influence of work environment on both individual performance and work-life balance, as well as a positive and significant influence of work-life balance on individual performance. Additionally, Perceived Organizational Support enhances the connection between the work environment and work-life balance, as well as individual performance. Moreover, this study demonstrates that career anxiety undermines the relationship between work-life balance and individual performance.